2020
DOI: 10.18805/ijare.a-520
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Evaluation of Mungbean [Vigna radiata (L.) Wilczek] Germplasm through Morphological and Agronomic Characters

Abstract: The study was conducted to assess the genetic diversity based on morphological and agronomic characters among 185 mungbean accessions by multivariate analysis such as cluster analysis and principal component analysis. The results exhibited that hierarchical cluster analysis divided into 7 clusters among the germplasm. The maximum number of accessions was observed in Cluster I with 60 accessions followed by Cluster II and Cluster III consists of 42 and 38 accessions, respectively. Cluster IV and VI comprised 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
3
2
0
Order By: Relevance
“…A similar result was revealed by Azam et al [11]. The estimated high CV observed in our research shows the large size of heterogeneity confirmed by Tripathi et al [38] and Win et al [44]. The variability of flowering time was repeated by Kanavi et al [33] from 33 to 53 days, and Win et al [34] from 31 to 75 days.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A similar result was revealed by Azam et al [11]. The estimated high CV observed in our research shows the large size of heterogeneity confirmed by Tripathi et al [38] and Win et al [44]. The variability of flowering time was repeated by Kanavi et al [33] from 33 to 53 days, and Win et al [34] from 31 to 75 days.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that crossing between outstanding genotypes of the abovementioned variety of varied cluster couples could produce appropriate recombinants for developing highyielding mungbean cultivars. The findings of this study were quite related to those of many investigations, such as Tahir et al [42], who described five clusters of 254 genotypes in mungbean; seven clusters of 196 genotypes in mungbean were described by Win et al [44], seven clusters of 84 genotypes in mungbean were described by Sarkar and Kundagrami [28], and eleven clusters of 80 genotypes in mungbean were described by Sen and De [55]. These data reveal the significant number of genetic variations among the examined mungbean accessions and provides an excellent chance for the selection of parents.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to this result the findings of Gokulakrishnan et al (2012) reported seed yield per plant had maximum contribution (63.67%) towards genetic divergence. These results were consonance by the findings of Win et al (2020).The 40 genotypes were divided into 7 groups according to Tocher's technique based on genetic distance (table 1). The cluster I, II, IV and V were poly genotypic, while clusters III, VI and VII were mono genotypic (1 genotype in each).…”
Section: Genetic Divergencesupporting
confidence: 74%
“…Principal component analysis showed that the first three components contributed highly to the phenotypic variation and cumulatively accounted for 83.4% of the total variation among the studied traits. Lower principal component values were recorded in V.radiata study with the first three principal components explaining 70% of the total variation [43]. PCA analysis indicated the contribution of individual traits toward the phenotypic divergence of the mung bean genotypes.…”
Section: Discussionmentioning
confidence: 75%